Interaction of Encephalomyocarditis Virus with Ultraviolet-irradiated Host Cells - Balduzzi, P. C. (1967)
Ultraviolet light (UV) impaired the capacity of L cells to support growth of encephalomyocarditis virus. The loss of capacity was partially restored by high multiplicity of infection (MOI). This phenomenon was not due to an increased probability of an infectious virus particle reaching a site of replication undamaged by UV, since UV-inactivated virus at high MOI induced restoration of the capacity to support multiplication of nonirradiated virus adsorbed at low MOI. Multiplicity reactivation of UV-irradiated virus did not play a role in this phenomenon since restoration of capacity took place without multiplication of the UV-irradiated restoring virus. The evidence indicates that restoration of capacity was not due to viral interactions involving genetic exchange. The ability to restore capacity was a property more radioresistant than infectivity, suggesting that the former is a function only of part of the viral genome.